KOMPAS DIGITAL DENGAN OUTPUT SUARA BERBASIS MIKROKONTROLER AT89S52 - Fahmi Fardiyan Arief; Muchlas Muchlas; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
In this paper, the design of digital compass with voice output is described, so that the blind can also use it. The digital compass is designed based on up-graded conventional compass. In the axis direction of conventional compass be added a disc as source of wind direction information, and phototransistor as sensor. The digital compass system is designed, based on AT89S52 microcontroller, as control of all interfaces and read sensor. The LCD component is used as display and ISD 2590 IC as voice recorder. The IC can record with maximum capacity 90 seconds. The voices output of compass is divided into 8 direction from the north, southwest, west and the next. The result showed that the design of digital compass work as like conventional compass completely by voice feature.